PENGARUH TEKTONIK PADA RUNTUNAN ENDAPAN ALUVIAL DEPRESI PADANGSIDEMPUAN, SUMATERA UTARA - Lumbanbatu, Ungkap M; Basri, C; Hidayat, S.; Siregar, Darwin A (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The investigated area, that is so called Padangsidempuan depression has been filled up by unconsolidated fluvial sediments. The sediments can be distinguished into five different environments, these are flood basin deposit, flood plain deposit, palaeo channel deposit, swamp deposit and colluvium deposit. To understand the influence of tectonic activities on lithological succession of the studied area several profiles were made. It reveals, that lithological successions have been disturbed by tectonic activities such as subsidence and uplifted. Subsidence can be identified by alternating of swamp facies deposit within different stratigraphic position and superimposed of the Batang Toru river on the palaeo channel deposit three (Ch-3). Further more the effect of uplifting caused palaeo channel deposit shifting horizontally. The data show that the tectonic activities in the studied area are not so very intensive. Keywords: quarternary tectonics, palaeo channels, pull-apart basin, sedimentary sequences